2005
DOI: 10.1016/j.mod.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of the eukaryotic translation initiation factors belonging to eIF4 families

Abstract: Protein synthesis in eukaryotic cells is fundamental for gene expression. This process involves the binding of an mRNA molecule to the small ribosomal subunit in a group of reactions catalyzed by eukaryotic translation initiation factors (eIF) eIF4. To date, the role of each of the four eIF4, i.e. eIF4E, eIF4G, eIF4A and eIF4B, is well established. However, with the advent of genome-wide sequencing projects of various organisms, families of genes for each translation initiation factor have been identified. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 116 publications
(212 reference statements)
1
105
0
5
Order By: Relevance
“…4 The exact role(s) of the RNA helicase, eIF4A, in initiation is incompletely defined but putative tasks for this peptide include dissociation of higher order RNA structure to enhance cap binding, and in scanning of 43S complex components from the cap to the start codon. 7,8 As might be expected, the activity of the cap-binding complex is controlled and can be modulated by regulatory proteins to augment or diminish translational gene expression. 1 We serendipitously discovered that bunyavirus N serves as a translation initiation factor when the expression of various reporter genes was curiously amplified in the presence of N. 9 Systematic analysis of the phenomenon indicated that N augments the translational expression of mRNA by either mimicking or obviating the requirement for the activities of the cap-binding complex.…”
Section: Bunyavirus N Protein Is a Translation Initiation Factormentioning
confidence: 90%
“…4 The exact role(s) of the RNA helicase, eIF4A, in initiation is incompletely defined but putative tasks for this peptide include dissociation of higher order RNA structure to enhance cap binding, and in scanning of 43S complex components from the cap to the start codon. 7,8 As might be expected, the activity of the cap-binding complex is controlled and can be modulated by regulatory proteins to augment or diminish translational gene expression. 1 We serendipitously discovered that bunyavirus N serves as a translation initiation factor when the expression of various reporter genes was curiously amplified in the presence of N. 9 Systematic analysis of the phenomenon indicated that N augments the translational expression of mRNA by either mimicking or obviating the requirement for the activities of the cap-binding complex.…”
Section: Bunyavirus N Protein Is a Translation Initiation Factormentioning
confidence: 90%
“…Hernández and Vazquez-Pianzola (29) have suggested that there is one eIF4E family member in each organism that is ubiquitously and constitutively expressed to carry out general translation and that others are involved in specialized functions, both translational and non-translational. Examples of this are beginning to emerge (Table 1).…”
Section: Physiological Roles For Specific Eif4e Family Membersmentioning
confidence: 99%
“…Mammalian eIF4F complexes contain eIF4A, the prototype of the DEAD box helicase family (7,8); however, plant eIF4A is loosely associated and is easily removed during purification (9). eIF4G is a multifunctional protein that is an important structural platform for the assembly or nucleation of several initiation factors (eIF4A, eIF3, eIF4B, eIF5, and poly(A)-binding protein) and interaction with the 40 S ribosome during the initiation process (10,11). Furthermore, in mammals there is also interaction of eIF4G with MNK kinase that then phosphorylates associated eIF4E (12).…”
mentioning
confidence: 99%